Impact of Neighborhood Environments on Health Consciousness, Information Seeking, and Attitudes among US-Born and Non–US-Born Free Clinic Patients. Issue 12 (December 2015) - Kamimura, Akiko; Ashby, Jeanie; Jess, Allison; Trinh, Ha Ngoc; Nourian, Maziar M.; Finlayson, Sarah Yukie; Prudencio, Liana; Reel, Justine J.
Abstract : Objectives: This study examined the impact of neighborhood environments on health consciousness, information seeking, and attitudes among uninsured free clinic patients to better understand the specific needs of the population for health promotion and prevention efforts. Methods: US-born English-speaking, non–US-born English-speaking, and Spanish-speaking free clinic patients completed a self-administered survey using reliable measures in autumn 2014 (N = 769). Results: The results of this study suggest that social cohesion is positively associated with health consciousness, information seeking, and attitudes. Lower levels of available healthy food in the community were associated with higher levels of health consciousness. Although Spanish speakers reported lower levels of the availability of healthy food, social cohesion, and access to the Internet or text messaging compared with US-born or non–US-born English speakers, they were more likely to be health conscious and have higher levels of health information seeking. Spanish speakers as well as non–US-born English speakers, were more likely to attend health education classes compared with US-born English speakers. Conclusions: Health education programs for free clinic patients should include strategies to increase social cohesion. Health education programs should consider the diverse needs of these individual populations to maximize the effectiveness of the programs for free clinic patients. Abstract : This study provides an overview of the impact of neighborhood environments on health consciousness, information seeking, and attitudes among patients of free clinics that provide free or reduced-fee primary care services to the uninsured or underinsured. Previous studies strongly recommend providing much needed health education and promotion to free clinic patients on a variety of chronic health issues. Focusing on health consciousness, information seeking, and attitudes is useful for developing effective health promotion programs. Supplemental digital content is available in the text.